Perbandingan hukum perampasan aset hasil tindak pidana korupsi di Indonesia, Singapura Dan Hongkong - Manguni WD Sinulingga; Jelly Leviza (Jurnal Normatif, 2023)
Corruption in law is a chronic issue with corrosive effects. In Indonesia, there institutions involved in handling criminal acts of corruption; the prosecutor`s Office, the Police, and the Corruption Eradication Commission (KPK). However, corruption cases in Indonesia continue to increase and fluctuate in their eradication efforts. The KPK is the main institution tasked with combating corruption in Indonesia, but it is perceived as not yet maximizing the seizure of assets resulting from corrupt activities. Singapore has a reputation for being stringent in combating corruption, boasting a powerful anti-corruption institution known as the Corrupt Practices Investigation Bureau (CPIB), which holds authority to investigate and prosecute corruption cases without political intervention. Hong Kong has an Independent Commission Against Corruption (ICAC) that has significantly succeeded in eradicating corruption. A comparative study of laws regarding the confiscation of assets resulting from acts of corruption in Indonesia, Singapore, and Hong Kong is needed to identify similarities, differences, and to analyze the similarities and differences in asset seizure resulting from corruption between the Indonesian Corruption Eradication Commission and the Corrupt Practices Investigation Bureau Singapore, and the Independent Commission Against Corruption Hong Kong